Novel psychoactive substances-related presentations to the emergency departments of the European drug emergencies network plus (Euro-DEN plus) over the six-year period 2014–2019. (2nd December 2022) - Crulli, Benjamin; Dines, Alison M.; Blanco, Georgina; Giraudon, Isabelle; Eyer, Florian; Liechti, Matthias E.; Miró, Òscar; Hovda, Knut E.; Heyerdahl, Fridtjof; Yates, Christopher; Vallersnes, Odd Martin; Wood, David M.; et al.
Abstract: Introduction: Novel psychoactive substances (NPS) have been increasingly reported in the last 15–20 years. We aimed to describe presentations to the emergency department (ED) with acute recreational drug toxicity involving NPS. Methods: Data were extracted from the European Drug Emergencies Network (Euro-DEN) Plus database for all presentations to ED (36 EDs in 24 European countries) with acute toxicity between January 2014 and December 2019. Patient demographics, agents involved, and clinical outcomes were described and the subgroup of presentations involving NPS was compared with the rest of the cohort. Results: Out of 43, 633 Euro-DEN Plus presentations, 3304 (7.6%) involved at least one NPS. Agents were identified mainly based on self-report or clinical presentation, with analytical confirmation being performed only in 17.9% of NPS presentations. The proportion of NPS presentations varied by centre (0–48.8%). For centres where data were available for all 6 years, NPS-related presentations peaked in 2015 (11.9%). In 2014, 78.4% of NPS agents reported were cathinones, while only 3.4% were synthetic cannabinoids (SCs); conversely, in 2019 only 11.6% of NPS agents reported were cathinones, while 72.2% were SCs. NPS-related presentations involved younger patients (median 30 (23–37) vs. 32 (25–40) years, p < 0.001) and more males (84.8 vs . 75.8%, p < 0.001) compared with the rest of the cohort. Patients presenting to ED after using NPS were more likely to self-discharge (22.8 vs. 15.1%), less likely to be admitted to critical care (3.6 vs . 6.1%) but had a longer length of stay in hospital (median 5.1 (2.7–18.7) vs. 4.7 (2.5–9.2) h, p < 0.001). Death occurred in 0.5% of all presentations involving NPS and in 0.4% of non-NPS presentations. Conclusions: This large multicentre series of NPS presentations to European EDs showed marked geographical variation and changes over time in the proportion of presentations to ED involving NPS, as well as the proportion of NPS subgroups.